تحديد وقت الصيانه الوقائية الامثل في شركة الهلال الصناعية المحدوده - ناصر, عمر محمد (Journal of Economics and Administrative Sciences, 2010)
The main target of this paper is to determine the optimum time for preventive maintenance on machines. Tow methods has been implemented estimating the optimum time duration for preventive maintenance . the first techniques use scheduling depending on data concerning the machine maintenance cost and halted cost from the production reach to the optimum time for maintenance which reflect the minimum cost. Where as the second techniques depends on reability function to estimate the optimum duration time which reflect the minimum cost. The tow techniques above by which we count on in fixing the preventive maintenance both give same result . we also prove that the scheduling method best than the reability function .